2008
DOI: 10.4012/dmj.27.549
|View full text |Cite
|
Sign up to set email alerts
|

3D Morphological Measurements of Dental Casts with Occlusal Relationship using Microfocus X-ray CT

Abstract: In the diagnosis of dental occlusion, it is necessary to quantitatively measure interocclusal contacts and transfer them to a computer model. In this aspect, three-dimensional computer models of upper and lower dental casts play a significant role. In this study, we proposed a new method to measure occlusal interaction by using a microfocus X-ray CT technique. Measurement accuracy was determined as ±0.03 mm in comparison with a coordinate measuring machine. A superimposition procedure for two sets of three-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
8
0
2
Order By: Relevance
“…Diese Aussage verdeutlicht wiederum die Abhängigkeit der elektronischen Objektabtastung von den Materialeigenschaften des verwendeten Abformmaterials. Erste Studien von Kamegawa et al zeigten anhand von CT-Untersuchungen zudem, dass okklusale Beziehungen mit dieser Untersuchungsmethodik quantitativ gut beurteilt werden können [14,15].…”
Section: Impression Materials and Impression Traysunclassified
See 1 more Smart Citation
“…Diese Aussage verdeutlicht wiederum die Abhängigkeit der elektronischen Objektabtastung von den Materialeigenschaften des verwendeten Abformmaterials. Erste Studien von Kamegawa et al zeigten anhand von CT-Untersuchungen zudem, dass okklusale Beziehungen mit dieser Untersuchungsmethodik quantitativ gut beurteilt werden können [14,15].…”
Section: Impression Materials and Impression Traysunclassified
“…The first studies conducted by Kamegawa et al using CT also showed that occlusal relationships can be assessed to a high standard with this examination method [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Very few reports have been published regarding the application of digital technology for the process of impression and interocclusal recording in edentulous patients. When using digital technology for the process of interocclusal recording, a common technique included additionally scanning an interocclusal record whose negative could then be used to correctly align both arches . Interocclusal records, due to their dimension and elasticity, were bound to introduce errors when used to align the maxilla and mandible .…”
Section: Discussionmentioning
confidence: 99%
“…They evaluated its reliability and found similar differences between CT scanning and manual measurements on plaster models. Kamegawa et al28 compared the accuracy evaluation using a microfocus X-ray CT technique and a conventional 3D optical scanner. The microfocus X-ray CT provided sufficient accuracy in dental occlusion diagnosis and quantitative clinical assessment of occlusal treatment 29…”
Section: Discussionmentioning
confidence: 99%